Chorea Associated with Diabetic Striatopathy in an Elderly Female: A Case Report - Islam, Md Rashedul; Rahman, Tanbin; Hossen Khan, Mohammad Sakhawat (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Diabetic striatopathy is a rare manifestation of diabetes mellitus. The disease commonly affects individuals of Asian descent, female, and the elderly. Patients usually present with hemiballism-hemichorea caused by hyperosmolar hyperglycemic state. Prompt recognition of a hyperglycemiainduced hemiballism-hemichorea is essential because the symptoms are reversible with correction of hyperglycemia. Diagnosis is possible based on blood reports and neuroimaging findings. J Bangladesh Coll Phys Surg 2022; 40: 65-67